2018
DOI: 10.3389/fmicb.2018.00178
|View full text |Cite
|
Sign up to set email alerts
|

HERVs New Role in Cancer: From Accused Perpetrators to Cheerful Protectors

Abstract: Initial indications that retroviruses are connected to neoplastic transformation were seen more than a century ago. This concept has also been tested for endogenized retroviruses (ERVs) that are abundantly expressed in many transformed cells. In healthy cells, ERV expression is commonly prevented by DNA methylation and other epigenetic control mechanisms. ERVs are remnants of former exogenous forms that invaded the germ line of the host and have since been vertically transmitted. Several examples of ERV-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 85 publications
0
83
0
Order By: Relevance
“…Some HERV sequences have oncogenic properties; yet treating cancer cells with methyltransferase inhibitors increases HERV RNA and DNA. Like infectious agents, the HERV-derived nucleic acids in the cytoplasm activate innate immune responses that produce tumor cell apoptosis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Some HERV sequences have oncogenic properties; yet treating cancer cells with methyltransferase inhibitors increases HERV RNA and DNA. Like infectious agents, the HERV-derived nucleic acids in the cytoplasm activate innate immune responses that produce tumor cell apoptosis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…32 HERV activation has also been reported in breast cancer, lymphoma, melanoma, ovarian cancer and prostate cancer, and the expression of env proteins can be involved in tumorigenesis via inducing cell-cell fusion. 33 In addition, it is known that sequences derived from HERVs can be a trigger of cancers if partial sequences of HERVs or HERV itself translocates to regulatory regions of oncogenes. 33 Tomlins et al reported that a translocation of HERV-K upstream of ETS translocation variant 1 caused cancerogenesis via enhanced expression of ETS translocation variant 1.…”
Section: Endogenous Retroviruses In Human Genomementioning
confidence: 99%
“…33 In addition, it is known that sequences derived from HERVs can be a trigger of cancers if partial sequences of HERVs or HERV itself translocates to regulatory regions of oncogenes. 33 Tomlins et al reported that a translocation of HERV-K upstream of ETS translocation variant 1 caused cancerogenesis via enhanced expression of ETS translocation variant 1. 34 HERV-K env genes originate 2 proteins (np9 and rec) with a different length by alternative splicing, and np9 proteins present 292bp deletion but rec is not ( Figure 1B).…”
Section: Endogenous Retroviruses In Human Genomementioning
confidence: 99%
“…HERVs have been mainly taken into account for their role in the molecular evolution of genomes [ 14 ]. However, in the last decades, several studies have underlined their involvement in the etiopathogenesis of complex diseases, such as cancer [ 15 , 16 ], autoimmune diseases [ 17 ], type 1 diabetes [ 18 ], and neurological and psychiatric disorders [ 19 ].…”
Section: Introductionmentioning
confidence: 99%